Γενιά του '70. Τόμος Β΄ : πεζός λόγος - Παναγιώτου, Γιώργος Α. (Λογοτεχνία, 1979)
Κείμενα των: Αντωνίου -- Γιατρομανωλάκης -- Δαμίγος -- Δεληγεώργη -- Δημητριάδης -- Δούκα -- Δρακονταειδης -- Θεοφίλου -- Καζαντζής -- Καραβίδας -- Κοροβέσης -- Κουτρουμπούσης -- Κυριακίδης -- Λάγκε -- Μεγάλου -- Μήτρας -- Μήτσορα -- Νόλλας -- Παπαδάκης -- Παπαδημητρίου -- Πλασσαρα -- Σουλιώτης -- Σουρούνης -- Τσατσούλα